Nanolocalization: Toward High‐Speed Nanoscopic Particle Tracking via Time‐Resolved Detection of Directional Scattering (Laser Photonics Rev. 14(9)/2020). Issue 9 (9th September 2020) - Beck, Paul; Neugebauer, Martin; Banzer, Peter
Abstract : Ultrafast hide‐and‐seek in nanostructured light fields is demonstrated by Peter Banzer and co‐workers in article number 2000110 . A nanoparticle of sub‐wavelength dimensions is placed in a tailored electromagnetic field landscape. High‐speed detection of light scattered directionally by the dielectric nanoparticle in a position‐dependent manner enables retrieval of the particle position with ultra‐high spatial and temporal accuracy.